Hypothyroidism correlates with osteoporosis: potential involvement of lipid mediators - Leng, Pengyuan; Qiu, Ying; Zhou, Mengxue; Zhu, Yuhang; Yin, Na; Zhou, Mingming; Wu, Weili; Liu, Min (Frontiers in Medicine, 2024)
Background: Observational studies have demonstrated a correlation between thyroid dysfunction and osteoporosis (OP); however, the underlying causality has yet to be fully elucidated.The necessary dataset was sourced from public databases. Initially, instrumental variables (IVs) were selected based on three primary hypotheses.Subsequently, Cochran's Q test was employed to exclude IVs exhibiting heterogeneity.The MR-PRESSO test and the leave-one-out sensitivity test were further applied to detect potential pleiotropy. Inverse variance was utilized for the analysis. This study primarily utilized the inverse variance weighted (IVW) model for Mendelian analysis.Since Type 1 diabetes mellitus can also contribute to the development of osteoporosis, this study additionally employed multivariate Mendelian analysis. Furthermore, 249 circulating metabolites were selected for mediation analysis in the Mendelian randomization framework.Results: In this study, the two-sample Mendelian randomization (MR) analysis primarily employed the random-effects IVW model and demonstrated a causal relationship between hypothyroidism (OR=1.092, 95% CI: 1.049-1.137, P<0.001) and hyperthyroidism (OR=1.080, 95% CI: 1.026-1.137, P=0.003) with the risk of OP. No causal relationships were identified between FT3, FT4, TSH, and the risk of OP (P>0.05). The results of the multivariate Mendelian randomization (MVMR) analysis indicated that hyperthyroidism was no longer a risk factor for OP (OR=0.984, 95% CI: 0.918-1.055, P=0.657), whereas hypothyroidism persisted as a risk factor (OR=1.082, 95% CI: 1.021-1.147, P=0.008). The mediated Mendelian randomization analysis revealed that hypothyroidism may exert an indirect effect on OP via triglycerides in large VLDL, mediating approximately 2.47% of the effect.This study identifies a potential link between hypothyroidism and OP, possibly mediated indirectly via triglyceride levels in large VLDL. Further investigations are required to elucidate the direct or indirect causal mechanisms underlying this association.